Review of the science and practice of restoration in Argentina: increasing awareness of the discipline - Rovere, Adriana E. (Restoration ecology, 2015)
The objective of this work was to obtain an overview of studies on ecological restoration carried out in Argentina to date. By means of the Scopus database, we performed two literature searches, one in Spanish (restau* and Argentina) and the other in English (restor* and Argentina). Between 1996 and 2013, 105 publications were registered, representing 2% of publications in Biology and Ecology. Most of these appeared in international journals (87%), in English (86%), and 28% were coauthored with researchers from other countries, favoring visibility at an international level. We observed an increase in the number of studies per year over time, with a significant increase beginning in 2008. Of the 18 ecological regions in Argentina, we found studies relating to 12 as well as four studies relating to restoration in urban areas. This review of the literature is intended to increase awareness of restoration in Argentina and help identify current gaps relating either to this subject or to specific ecological regions.